Digitalization of school guidance in Algeria - Benbahi, Sara (The International tax journal, 2026)
This study examines the experience of digitalizing school guidance within the Algerian educational system, which was effectively launched during the 2023/2024 academic year. This reform represents a qualitative step toward modernizing educational services and strengthening transparency and fairness in student orientation. The research adopts a descriptive-analytical approach to explore the field reality of this digital transition. It focuses on achievements as well as the technical and human challenges encountered during implementation. The findings indicate a clear improvement in service quality. Family satisfaction rates increased from 78% to 88%, while file processing time decreased by 80%. However, challenges related to digital infrastructure in rural areas and the existing digital divide require further investment and comprehensive training programs. Such measures are necessary to ensure the sustainability of this transformation and to extend its benefits to all geographical regions.